Purification of Hydrogen from CO with Cu/ZSM-5 Adsorbents - Mihail Mihaylov; Elena Ivanova; Videlina Zdravkova; Stanislava Andonova; Nikola Drenchev; Kristina Chakarova; Radoslav Kefirov; Rositsa Kukeva; Radostina Stoyanova; Konstantin Hadjiivanov (Molecules, 2021)
The transition to a hydrogen economy requires the development of cost-effective methods for purifying hydrogen from CO. In this study, we explore the possibilities of Cu/ZSM-5 as an adsorbent for this purpose. Samples obtained by cation exchange from aqueous solution (AE) and solid-state exchange with CuCl (SE) were characterized by in situ EPR and FTIR, H2-TPR, CO-TPD, etc. The AE samples possess mainly isolated Cu2+ cations not adsorbing CO. Reduction generates Cu+ sites demonstrating different affinity to CO, with the strongest centres desorbing CO at about 350 °C. The SE samples have about twice higher Cu/Al ratios, as one H+ is exchanged with one Cu+ cation. Although some of the introduced Cu+ sites are oxidized to Cu2+ upon contact with air, they easily recover their original oxidation state after thermal treatment in vacuum or under inert gas stream. In addition, these Cu+ centres regenerate at relatively low temperatures. It is important that water does not block the CO adsorption sites because of the formation of Cu+(CO)(H2O)x complexes. Dynamic adsorption studies show that Cu/ZSM-5 selectively adsorbs CO in the presence of hydrogen. The results indicate that the SE samples are very perspective materials for purification of H2 from CO.